An optimized combination inspired by the wooden-barrel effect for Li-S pouch cells - Jian Tan; Zhiqiang Yao; Mingxin Ye; Jianfeng Shen (Cell Reports Physical Science, 2021)
Summary: Lithium-sulfur (Li-S) batteries are regarded as one of the most promising alternatives for next-generation energy storage and conversion due to the low cost of raw materials and high theoretical energy density. However, their practical applications have been plagued by rapid capacity decay, which is mainly ascribed to issues with the design and balance of components inside the batteries. In recent years, many advanced components have been reported, but few have been applied in practical Li-S batteries. Inspired by the wooden-barrel effect, in this perspective, we propose an optimized combination that integrates all advanced components into one system. For a better understanding of this topic, the typically advanced designs applied in Li-S pouch cells are summarized. Subsequently, the safety performance of Li-S pouch cells under extreme testing conditions are provided. Finally, our personal insights for the future development direction of Li-S pouch cells are proposed.